The role of ecological variation in driving divergence of sexual and non-sexual traits in the red-backed fairy-wren (Malurus melanocephalus) - Baldassarre, Daniel T; Thomassen, Henri A; Karubian, Jordan; Webster, Michael S (BMC evolutionary biology, 2013)
Many species exhibit geographic variation in sexual signals, and divergence in these traits may lead to speciation. Sexual signals may diverge due to differences in ecology if the environment constrains signal production or transmission. Alternatively, sexual signals may diverge stochastically through sexual selection or genetic drift, with little environmental influence. To distinguish between these alternatives we quantified variation in two putative sexual signals--tail length and plumage color--and a suite of non-sexual morphometric traits across the geographic range of the red-backed fairy-wren (Malurus melanocephalus). We then tested for associations between these traits and a number of environmental variables using generalized dissimilarity models. Variation in morphometric traits was explained well by environmental variation, irrespective of geographic distance between sites. Among putative signals, variation in plumage color was best explained by geographic distance, whereas tail length was best explained by environmental variation. Divergence in male plumage color was not coincident with the boundary between genetic lineages, but was greatest across a contact zone located 300 km east of the genetic boundary. Morphometric traits describing size and shape have likely been subject to ecological selection and thus appear to track local environmental variation regardless of subspecies identity. Ecological selection appears to have also influenced the evolution of tail length as a signal, but has played a limited role in shaping geographic variation in plumage color, consistent with stochastic divergence in concert with Fisherian selection on this trait. The lack of coincidence between the genetic boundary and the contact zone between plumage types suggests that the sexual plumage signal of one subspecies has introgressed into the genetic background of the other. Thus, this study provides insight into the various ways in which signal evolution may occur within a species, and the geographic patterns of signal variation that can arise, especially following secondary contact.